Combined Oral Contraceptives and Venous Thromboembolism: Review and Perspective to Mitigate the Risk - Morimont, Laure; Haguet, Hélène; Dogné, Jean-Michel; Gaspard, Ulysse; Douxfils, Jonathan (Frontiers in Endocrinology, 2021)
Many factors must be considered and discussed with the women when considering a contraceptive method. In addition to the efficacy, the tolerability and additional health benefits, the risk of venous thromboembolism is an important aspect of these medication that must be evaluated. Evidence suggesting that combined oral contraceptives were associated with an increased risk of thrombosis rapidly appeared after they were introduced on the market and numerous strategies were implemented to reduce this side effect. The dosage of the estrogen, i.e., ethinylestradiol, was significantly reduced, as it had been identified as the main contributor of this risk. New progestins were also synthetized, with the aim to provide a pharmacodynamic profile closer to the one of progesterone. However, it was demonstrated that the weak androgenic activity of these new compounds (e.g., desogestrel or gestodene), did not permit to counterbalance the effect of ethinylestradiol as did initial progestins such as levonorgestrel. Numerous studies have been done to assess the impact of the different estroprogestative combinations on hemostasis and it was demonstrated that women using combined oral contraceptives suffered from resistance towards activated protein C, an endogenous anticoagulant factor. Subsequently, the European Medicines Agency updated its guidelines on clinical investigation of steroid contraceptives in women and they recommended to evaluate the impact of new steroid contraceptives on sex hormone binding globulin, as well as on the resistance towards activated protein C resistance. In 2014, a European referral aimed to document the risk of thrombosis, and they concluded that the benefit-risk balance remained positive. Therefore, to date, no specific risk minimization strategies are recommended except a periodical re-evaluation of the risk which remains evasive. One rationale and affordable perspective which has already been considered in the past could be the implementation of a baseline screening of the prothrombotic state to provide the gynecologist with objective data to support the prescription of the more appropriate contraceptive method and to ensure a follow-up throughout woman’s life. Nevertheless, over the past ten years, novel therapeutical entities were marketed with the aim to provide a safe alternative in regards to the risk of thrombosis with combined oral contraceptive.